PENGARUH JENIS PEKERJAAN DAN PENDAPATAN ORANG TUA TERHADAP STATUS GIZI ANAK DI YAYASAN PENDIDIKAN MANDIRI JALAN DANAU SIOMBAK LABUHAN DELI MEDAN - Muhammad Sanusi Hasibuan; Masdalena Nasution; Suhartina Suhartina (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
Initiating a health-oriented development movement as a national development plan, the Indonesian government has proclaimed a healthy Indonesia in 2010. In line with efforts to improve child nutrition, national human resource-oriented development policies place an emphasis on improving people's nutritional status and addressing nutritional problems. Thus, the purpose of this study was to examine the effect of work and parental wealth on the eating habits of Medan Marelan Elementary School students. An analytical study using a cross-sectional (observational) research methodology was conducted to examine the impact of parents' occupation and income on their children's food intake. Univariate analysis and bivariate analysis were used to check the research data. The study found that the value of p = 0.9 was obtained from the findings of the chi-square test. These results indicate that p > α (0.05), based on this, the study of educational foundations running independently from 2022 at the Siombak Deli lake port shows that there is no substantial relationship between parents' income and children's nutritional health. Chi-square analysis yielded a significance level of p = 0.5. These findings indicate that the working conditions at Delis Lake Siombak Port have no effect on the nutritional status of children in 2022.